2017
DOI: 10.1002/jrs.5263
|View full text |Cite
|
Sign up to set email alerts
|

Analytical imaging of colour pigments used in Japanese woodblock prints using Raman microspectroscopy

Abstract: Ukiyo‐e printing is a traditional Japanese multicolour woodblock printing style that flourished during the 18th century. Although this genre subsequently experienced a decline, interest in it has since re‐emerged. However, the materials and carving and printing technologies originally used to produce ukiyo‐e prints remain unclear due to a lack of technical information. In this study, we performed non‐invasive molecular imaging of the colour pigments in recently reproduced and original ukiyo‐e prints using Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…1 PB is also a chronological marker since it was introduced in the Japanese woodblock printing process at the end of the 1820s. Few analytical studies were conducted on such artworks [2][3][4][5][6][7][8][9] but the common use of indigo and PB in Japanese paintings, alone or mixed together, has been observed. [10][11][12] The majority of the studies conducted on 19th century ukiyo-e have also identified or have traced the presence of PB in blue colors as the primary or as in mixtures to obtain different shades of blue, green, and violet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 PB is also a chronological marker since it was introduced in the Japanese woodblock printing process at the end of the 1820s. Few analytical studies were conducted on such artworks [2][3][4][5][6][7][8][9] but the common use of indigo and PB in Japanese paintings, alone or mixed together, has been observed. [10][11][12] The majority of the studies conducted on 19th century ukiyo-e have also identified or have traced the presence of PB in blue colors as the primary or as in mixtures to obtain different shades of blue, green, and violet.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The majority of the studies conducted on 19th century ukiyo-e have also identified or have traced the presence of PB in blue colors as the primary or as in mixtures to obtain different shades of blue, green, and violet. 2,7,[10][11][12][13] The mixture of indigo and PB, though, is barely considered in these studies although potentially present. Because indigo and PB are known to be very similar under the microscope, 14,15 different studies on their identification in mixture have been conducted for over 30 years on different artworks (textiles, paintings), but they mainly involved destructive analyses 16,17 or necessitate contact with the objects (Surface-enhanced Raman spectroscopy -SERS -analyses).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, Japanese woodblock prints have also attracted the attention of scholars and, more recently, scientists [1][2][3][4][5][6][7][8][9][10][11][12][13] . Driven by research questions such as the lightfastness of colors, the chronology of the use of certain pigments 11,12,14 , the introduction of new materials in Japan 4,11 , the understanding of the creation sequence of prints 4,13,15 , and the transition between the Edo period and the Meiji era 4 , researchers have developed analytical protocols with particular attention to the investigation of Japanese woodblock prints 1,4,5,14,15 .…”
mentioning
confidence: 99%
“…Minamikawa et al presented an analysis of imaging of color pigments used in Japanese woodblock prints using Raman microspectroscopy. Their results indicate that Raman microspectroscopy is a promising technique for detecting the original Ukiyo‐e print production technologies, which are currently unknown …”
Section: Art and Archaeologymentioning
confidence: 99%
“…Their results indicate that Raman microspectroscopy is a promising technique for detecting the original Ukiyo-e print production technologies, which are currently unknown. [137] 14.4 | Geological, archeological, and extraterrestial related samples Cao, Ling, and Ni presented a chemical and spectroscopic investigation of K-H 3 O-Na jarosite solid solutions applicable for Mars explorations. Near-IR and mid-IR spectra were also collected for the spectral library of Mars remote-sensing studies.…”
Section: Pigments Dyes Paints Fibres and Inksmentioning
confidence: 99%